Lability and solubility of uranium and thorium in soil - Ahmed, Hayam Mohamed Mahmoud (2014)
The approach used in this study tested the application of an isotope dilution technique (ID) as a means of measuring the labile U(VI) and Th pools in soils. Uranium and Th lability and solubility were investigated for two sets of soils. The first set (Field soils) consisted of thirty seven soil samples representing five contrasting local ecosystems; the second dataset (BGSc) included 40 soils sub-sampled from the British Geological Survey (BGS) archive. Field soil pore water samples were taken from soil columns held at close to field capacity to measure U and Th solubility and speciation; the effects of time, temperature and reducing conditions on Th and U speciation were investigated. Soils were extracted with foursingle extractants: CH3COONH4, EDTA, 0.43 M HNO3 and TMAH to determine their ability to solubilize labile U and Th. Solubility of Th and U varied with soil characteristics, influenced by pH, DOC, DIC and phosphate concentrations. The Kd values for Th and U varied by 4 and 3 orders of magnitude respectively over the range of soils studied. The formation of soluble uranyl carbonate complexes give rise to a strong positive correlation between U and DIC concentrations in soil solutions. This was particularly clear under anaerobic conditions and also at high temperatures which encouraged microbial activity and high CO2partial pressures. Isotopically exchangeable 238U(VI) (the ‘E-value’, UE) in the soils studied varied from 2.7 to 39.1% of the total soil U content. On average, over all groups of soils, CH3COONH4, EDTA and TMAH underestimated E-value by factors of 13.7, 9.5 and 1.6, respectively, while extraction with 0.43M HNO3 overestimated E-value by only a factor of 1.04. Thus, on average across a range of soils, dilute nitric acid gave the best estimate of E-value compared to other extractants. Generally, E-values for U(VI) did not correspond consistently with any single chemical extraction procedure although the degree of correspondence was soil-dependent. Using UEand ThTMAH as input parameters in the geochemical speciation model WHAM-VII improved the prediction of U and Th solubility compared to using the total metal content orthe pools extractable by (other) single extraction methods. Finally, preliminary experiments confirmed the validity of ID for measuring labile soil Th without disturbance of soil-solution equilibrium.